REVITALIZATION OF CULTURAL VALUES IN PUBLIC ADMINISTRATION REFORM (A STUDY OF CIVIL SERVANTS IN GORONTALO) - Novel Acub Umar; Asna Aneta; Nur Mohamad Kasim; Udin Hamim (Adisam Publisher, 2025)
Public administration reform aims to create a professional, efficient, and service-oriented bureaucracy. However, in its implementation, bureaucratic modernization often ignores local cultural values that have long been guidelines for work ethics, including for Civil Servants (PNS). This study examines the revitalization of cultural values in public administration reform, focusing on PNS in Gorontalo. This study uses a qualitative approach with a descriptive method, where data are collected through interviews, observations, and document analysis. The results of the study indicate that local cultural values of mutual cooperation, honesty, and the principle of harmony between customs, social norms, and religion still influence the work ethic of PNS in Gorontalo. However, the implementation of these values faces challenges in a bureaucratic system that increasingly prioritizes administrative procedures and compliance with formal regulations. Several factors that hinder cultural revitalization in public administration include rigid bureaucratic structures, lack of culture-based training, and low integration of cultural values in institutional policies. This study recommends a strategy for revitalizing cultural values in public administration reform, including through strengthening local wisdom-based training, developing culture-oriented leadership, and aligning regulations with the social values of society. With this approach, it is hoped that a bureaucracy can be formed that is not only modern and efficient, but also more inclusive, humanistic, and rooted in local cultural values.